Phylogenomic exploration of the relationships between strains of Mycobacterium avium subspecies paratuberculosis. (December 2016) - Bryant, Josephine; Thibault, Virginie; Smith, David; McLuckie, Joyce; Heron, Ian; Sevilla, Iker; Biet, Franck; Harris, Simon; Maskell, Duncan; Bentley, Stephen; Parkhill, Julian; Stevenson, Karen
Abstract Background Mycobacterium avium subspeciesparatuberculosis (Map ) is an infectious enteric pathogen that causes Johne's disease in livestock. Determining genetic diversity is prerequisite to understanding the epidemiology and biology ofMap . We performed the first whole genome sequencing (WGS) of 141 globalMap isolates that encompass the main molecular strain types currently reported. We investigated the phylogeny of theMap strains, the diversity of the genome and the limitations of commonly used genotyping methods. Results Single nucleotide polymorphism (SNP) and phylogenetic analyses confirmed two major lineages concordant with the former Type S and Type C designations. The Type I and Type III strain groups are subtypes of Type S, and Type B strains are a subtype of Type C and not restricted toBison species. We found that the genome-wide SNPs detected provided greater resolution between isolates than currently employed genotyping methods. Furthermore, the SNP used for IS1311 typing is not informative, as it is likely to have occurred after Type S and C strains diverged and does not assign all strains to the correct lineage. Mycobacterial Interspersed Repetitive Unit-Variable Number Tandem Repeat (MIRU-VNTR) differentiates Type S from Type C but provides limited resolution between isolates within these lineages and the polymorphisms detected do not necessarily accurately reflect the phylogenetic relationships between strains. WGS of passaged strains and coalescent analysis of the collection revealed a very high level of genetic stability, with the substitution rate estimated to be less than 0.5 SNPs per genome per year. Conclusions This study clarifies the phylogenetic relationships between the previously describedMap strain groups, and highlights the limitations of current genotyping techniques.Map isolates exhibit restricted genetic diversity and a substitution rate consistent with a monomorphic pathogen. WGS provides the ultimate level of resolution for differentiation between strains. However, WGS alone will not be sufficient for tracing and trackingMap infections, yet importantly it can provide a phylogenetic context for affirming epidemiological connections.